Constitutional Rights of Woman Commercial Sex Workers in Bending Sari Pekalongan - Bunga Desyana Pratami (Faculty of Sharia, State Islamic University KH. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2021)
This paper analyzes the fulfillment of the constitutional rights of women commercial sex workers and the responsibility of the State in fulfilling the constitutional rights of women commercial sex workers in Bendan Sari, Pekalongan City. This empirical juridical research uses a qualitative approach. Collecting data using observation, interviews and literature study. The analysis uses an interactive model. The results show that the constitutional rights of women commercial sex workers in Bending Sari have not been fully fulfilled. For example, the right to a decent life, the right to health care and the right not to be discriminated against. This is due to the local government's rejection of their existence as Commercial Sex Workers, so they do not get the space and opportunity to fight for their rights. The responsibility of the state, in this case is the Pekalongan City government to fulfill the constitutional rights of Women Commercial Sex Workers in Bendan Sari carried out by prevention and guidance to them through social services by providing training and business capital. The aim is that the female commercial sex workers who have been trained have the skills and willingness not to return to work as sex workers, so that they can continue to live a better, decent and healthy life. In addition, to protect the rights of citizens, in this case the community in the vicinity of the Bendan Sari prostitution area.